Characterization of phases of aluminized nickel base superalloys - Göken, Mathias; et al. (Surface & Coatings Technology, 2003)
Aluminum rich coatings, built up by a diffusion zone and a NiAl-cover layer, can protect the surface of turbine blades against oxidation. Within the single crystalline substrate and the adjacent layer, phases in the range of several tens of nanometers up to a few micrometers develop during production and operation of the turbine blade, were characterized. Investigations with transmission electron microscopy, nanoindentation and local crystal orientation mapping with a scanning electron microscope have been carried out in order to determine composition, morphology and distribution of the different phases. The diffusion zone has in general a defined orientation relative to the superalloy substrate and is built up by at least three phases embedded in a softer matrix, with significant differences in nanohardness. Local internal stress states in the diffusion zone are estimated. The NiAl-cover layer is a coarse columnar grained, non-textured B2 ordered intermetallic NiAl-phase. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.tech.IW.LWAW.charac
Keywords: Electron back scattered diffraction; Nanoindentation; Nanostructure; Nickel alloy; Phase transitions; Transmission electron microscopy